1994
DOI: 10.1177/002076409404000303
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Migrant Status (Refugee or Immigrant) to Mental Health

Abstract: This study investigated and compared mental health levels among refugees and immigrants living in New Zealand. One hundred and twenty-nine Indochinese refugees, 57 Pacific Island immigrants and 63 British immigrants to New Zealand were surveyed. A questionnaire and the Hopkins Symptom Checklist-25 (HSCL-25) in English and in three Indochinese translations, were administered face-to-face. The hypothesis that migrant status (being a refugee or immigrant) affects mental health and that refugees experience more em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 29 publications
1
22
1
2
Order By: Relevance
“…Similar mixed results are found among immigrants to New Zealand. Pernice and Brook (1994) find the mental health of a sample of Pacific Island immigrants in New Zealand to be as low as that of a sample of Southeast Asian refugees, and significantly lower than that of British immigrants. In contrast, Graves and Graves (1985) surveyed Samoans, Cook Islanders and native-born New Zealanders of European background, and found the Pacific Islanders to have significantly fewer psychosomatic symptoms of health problems than did the European New Zealanders.…”
Section: The Association Between Mental Health and Migrationcontrasting
confidence: 55%
“…Similar mixed results are found among immigrants to New Zealand. Pernice and Brook (1994) find the mental health of a sample of Pacific Island immigrants in New Zealand to be as low as that of a sample of Southeast Asian refugees, and significantly lower than that of British immigrants. In contrast, Graves and Graves (1985) surveyed Samoans, Cook Islanders and native-born New Zealanders of European background, and found the Pacific Islanders to have significantly fewer psychosomatic symptoms of health problems than did the European New Zealanders.…”
Section: The Association Between Mental Health and Migrationcontrasting
confidence: 55%
“…For example, Steel et al (2002) found that Vietnamese refugees in Australia who experienced more than three traumatic events had a heightened risk of mental illness even 10 years post-resettlement compared with people with no trauma exposure. Similarly, Pernice and Brook (1994) found high levels of anxiety and depression in their study of recently arrived refugees in New Zealand. Allan (2014) indicates that there are high levels of depression, anxiety, and guilt among refugee populations in Australia as well.…”
Section: Introductionmentioning
confidence: 87%
“…Pernice and Brook (1994) Islanders may be due to their experience of discrimination and unemployment, which were amongst the most significant correlates of mental disorders for the pooled sample (Pernice and Brook, 1996). Amongst both the Southeast Asian refugees and Pacific Island migrants, 30 percent of respondents reported experiencing discrimination in either their workplace or from health professionals.…”
Section: Previous Literaturementioning
confidence: 99%